KONTRIBUSI NILAI NILAI KARAKTER DALAM KITAB TA’LIM MUTA’ALIM TERHADAP SANTRI PONDOK PESANTREN AL MAWADDAH WARRAHMAH KOLAKA - Ade Saputra; Askahar Askahar; Suhardin Suhardin (IAI Al-Mawaddah Warrahmah Kolaka, 2023)
Contributions are donations that can be in the form of material, thoughts, and actions. Character education is education that fosters a student in developing the goodness that is in him, because basically all humans have the potential for goodness that is in each of us, and with education that potential for goodness can be raised and developed. The book of ta'lim muta'llim is one of the reference books that is widely used in Islamic boarding schools, in this book it discusses the things that must be done by students in achieving blessed knowledge. The formulation of the problem in this study, what are the values of character education contained in the book of ta’lim muta'llim and how is the contribution of the book of ta'lim muta'llim in shaping the character of the students of Al Mawaddah Islamic boarding school Warrahmah Kolaka. The purpose of the research is to find out the values of character education contained in the book of the ta'lim muta'llim and its contribution in shaping the character of the students of the Al Mawaddah Warrahmah Kolaka Islamic boarding school. The results of the study show that the character values in the ta'lim muta'llim book, especially in the discussion of the exaltation of knowledge and teachers, in this chapter explain a number of things which are then instilled in every student at the Al Mawaddah Warrahmah Kolaka Islamic boarding school as a form of character education. As for some of these things, namely, (1) may not pass in front of the teacher, even if they are forced to pass in front of the teacher, they want to ask permission in our tradition mello tabe, (2) do not occupy the teacher's seat, (3) do not start the speaker when we are called to face him other than with his permission, (4) not to look at his face when dealing with him, (5) not to ask something that can make the teacher bored when he is tired, (6) be disciplined, (7) seek the teacher's approval, and (8) trying not to make the teacher angry.